Pharmacological and toxicological profile of opioid-treated, chronic low back pain patients entering a mindfulness intervention randomized controlled trial - Zgierska, MD, PhD, Aleksandra; Wallace, PharmD, BCACP, Margaret L.; Burzinski, MS, Cindy A.; Cox, BS, Jennifer; Backonja, MD, Miroslav (Journal of Opioid Management, 2014)
Objective: Refractory chronic low back pain (CLBP) often leads to treatment with long-term opioids. Our goal was to describe the pharmaco-toxicological profile of opioid-treated CLBP patients and identify potential areas for care optimization. Design: Cross-sectional analysis. Setting: Outpatient primary care. Participants: CLBP patients prescribed ≥ 30 mg/d of morphine-equivalent dose (MED) for ≥3 months. Outcome Measures: Self-reported clinical, medication (verified) and substance use, and urine drug testing (UDT) data were collected. Results: Participants (N = 35) were 51.8 ± 9.7 years old, 80 percent female with CLBP for 14.2 ± 10.1 years, treated with opioids for 7.9 ± 5.7 years, with severe disability (Oswestry Disability Index score: 66.7 ± 11.4), and average pain score of 5.6 ± 1.5 (0-10 rating scale). Participants reported using tobacco (N = 14), alcohol (N = 9) and illicit drugs or unprescribed medications (N = 10). On average, participants took 13.4 ± 6.8 daily medications, including 4.7 ± 1.8 pain-modulating and 4.7 ± 2.0 sedating medications. Among prescribed opioids, 57.1 percent were long-acting and 91.4 percent were short-acting, with a total of 144.5 ± 127.8 mg/d of MED. Sixteen participants were prescribed benzodiazepines and/or zolpidem/zaleplon. Fifteen participants had UDT positive for illicit drugs or unprescribed medications; in addition, eight tested positive for alcohol and 19 for cotinine. Compared to those with negative UDTs, those with positive UDTs (N = 15) received lower daily “total” and “extended release” opioid doses, and were more likely to test positive for cotinine (p < 0.05). Conclusions: Study findings corroborate existing evidence for high medication burden and high likelihood of substance misuse among opioid-treated CLBP patients. Further research is needed to help understand causality and ways to optimize care and clinical outcomes.